Case Study Of Consumer Broadband Product Launch For Maxis - Singh, Hargharan (2007)
This case study is done to understand the effectiveness of the comprehensive consumer broadband product launch process for a large multinational enterprise like Maxis as compared other broadband providers.This project was written based on secondary data and also from first hand data colletcted from survey. The purpose for the survey was to gauge the awareness among Malaysian people on broadband, identify the key value for broadband and customers\' needs and wants.